Comparison of the dental sealing abilities of three bioceramic sealants in the root canal: An in-vitro study (International Journal of Food and Nutritional Sciences, 2022)
The main objective of endodontic treatment is to prevent further infection or reinfection by eliminating microorganisms within the root canal system. Proper endodontic treatment could prevent apical and coronal penetration of fluids and microorganisms. Endodontic sealer is vital components of root canal obturation to establish a fluid-tight seal. Bioceramic-based root canal sealers are considered to be an advantageous technology in endodontics and have been found to be both biocompatible and comparable to other commercial sealers. The aim of this study was to compare the adhesion of three bioceramic sealers within the root canal system. Method: Endodontically treated teeth were obturated using three types of bioceramic sealers and then divided into three groups. Specimens were then observed using a scanning electron microscope, and the attachment distance was measured using ImageJ. Results: The three groups exhibited were statistically significant differences (p